Digestible Sulfur Amino Acid Requirements for Maintenance in the Starting Turkey - Brown, J.; Firman, J.; Sun, S.; Kamyab, A. (International Journal of Poultry Science, 2005)
Amino acid requirement data can be determined in multiple fashions. One method for determining amino acid requirement is through modeling. A portion of the data required for a comprehensive model is the maintenance requirement. Two studies were conducted to determine the maintenance requirement for the sulfur amino acids during the starter period for turkeys. A low protein diet was formulated so that different levels of total sulfur amino acids could be fed to young turkeys. A maintenance requirement of approximately 26 mg/bird/day was found in both experiments. This information, coupled with the amino acid requirements for growth, will allow for the construction of an effective model to predict amino acid requirements over a wide range of environment and physiological conditions.